2003
DOI: 10.1039/b212655a
|View full text |Cite
|
Sign up to set email alerts
|

Atomic spectrometry update. Environmental analysis

Abstract: This is the twentieth annual review published in JAAS of the application of atomic spectrometry to the chemical analysis of environmental samples. In the analysis of air, there is ongoing development of instrumentation for continuous emission monitoring and as a means of interrogating the composition of individual airborne particulates. Developments in mass spectrometry applications continue to be an active area of research where the advantages of low detection limits and abilities to perform isotopic measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 250 publications
2
30
0
1
Order By: Relevance
“…It is often impossible to determine the different chemical species in a system, due to the complexity of such analysis; in this instance fractionation, defined as the process of classification of an analyte according to physical and chemical properties may be a useful approach [51]. Kotas J., Stasicka Z., [68] made a summary of all the techniques available for the Cr speciation in solid matrix samples, while Hill et al [6] indicated a list of main elements and the relative techniques that can be used to measure them in various sample media. Below will be illustrated the various species of chromium and some techniques for illustration.…”
Section: Speciationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often impossible to determine the different chemical species in a system, due to the complexity of such analysis; in this instance fractionation, defined as the process of classification of an analyte according to physical and chemical properties may be a useful approach [51]. Kotas J., Stasicka Z., [68] made a summary of all the techniques available for the Cr speciation in solid matrix samples, while Hill et al [6] indicated a list of main elements and the relative techniques that can be used to measure them in various sample media. Below will be illustrated the various species of chromium and some techniques for illustration.…”
Section: Speciationmentioning
confidence: 99%
“…The selection of the measuring technique will depend highly on the detection limit of the expected concentrations of respective elements. Hill et al [6] made an extensive summary of all the available detection techniques and possibilities for various sampling types and element speciation.…”
Section: Total Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many analytical methods have been used in determination of arsenic species: AAS, ICP-MS, ICP-AES, the hyphenated systems with GC or HPLC, and the methods in combination with generation of hydrides HG [2]. The technique of hydride generation permits isolation of an element under determination from the interfering matrix and allows speciation-making use of the differences in the kinetics of hydride formation by As (III) and As (V) [3].…”
Section: Introductionmentioning
confidence: 99%
“…A number of analytical methods have been used for the purpose AAS, ICP-MS, ICP-AES, in combination with the technique of hydride generation HG [3]. The use of hydride generation as a technique for introduction of the analyte in spectrometric methods permits isolation of the element under determination from the interfering environmental matrix and determination of particular species on the basis of the di®erences in the kinetics of hydride generation by As(III) and As(V) [4], [5].…”
Section: Introductionmentioning
confidence: 99%